A report of three cases of untreated Graves’ disease associated with pancytopenia in Malaysia - Rafhati, Abdullah Noor; Chee, Keong See; Hoo, Fan Kee; Mohamed Badrulnizam, Long Bidin (Electronic Physician, 2014)
Generally, clinical presentations of Graves’ disease range from asymptomatic disease to overt symptomatic hyperthyroidism with heat intolerance, tremor, palpitation, weight loss, and increased appetite. However, atypical presentation of Graves’ disease with hematological system involvement, notably pancytopenia, is distinctly uncommon. Hereby, we present and discuss a series of three untreated cases of Graves’ disease clinically presented with pancytopenia and the hematological abnormalities that responded well to anti-thyroid treatment. With resolution of the thyrotoxic state, the hematological parameters improved simultaneously. Thus, it is crucial that anti-thyroid treatment be considered in patients with Graves’ disease and pancytopenia after a thorough hematological evaluation.